The Effect of The Zig-Zag Dribbling Training Method To Improve The Dribbling Skills of Players In The 13-15 Year Age Group At SSB Buazh FC Magetan - Yudha Bagus Prasetya Yudha; Lutfhi Abdil Khuddus; Mokhammad Nur Bawono; Achmad Widodo (Jurnal Pendidikan Jasmani (JPJ), 2026)
One of the many sports, a sport that is very popular in Indonesia is football, which is very popular among the Indonesian people. Football is a very popular team game where each team consists of eleven people and plays against each other with the aim of scoring as many goals as possible into the opponent's goal to win the match, thus it can be concluded that the main goal of playing football is to score goals to win. In playing soccer, players are required to be able to master the basic techniques of playing soccer, one of which is the technique of dribbling the ball, as well as understanding how to dribble the ball, players who are able to master the basic techniques of dribbling well will easily penetrate the opponent's area, thus creating opportunities to score goals, if players are able to master good basic techniques and are supported by good physical condition, they can be said to be good soccer players, because they can improve their performance and play well. At SSB Buazh FC Magetan, there are still many students who are not very good at mastering basic techniques, especially dribbling skills, when doing dribbling movements. The research design used a pre-test and post-test, with an experimental method. The population used in this study was 30 SSB Buazh FC players. The sample of this study as a whole was SSB Buazh FC players aged 13-15 years, totaling 25 people. Data analysis began with prerequisite testing using the one-sample Kolmogorov-Smirnov and Shaphiro-Wilk test before conducting the paired sample t-test. This study uses a t-test to evaluate the influence, the data is evaluated as an independent variable: zig-zag dribbling training method (X) and a dependent variable: dribbling skills (Y). The Kolmogorov-Smirnov test has a Sig. value of 0.190 and the Shapiro-Wilk test has a Sig. value of 0.106, which means it is above the threshold of 0.05. The significance value (Sig.) for each normality test method for both pretest and posttest data is all above 0.05. Since both Sig. values are greater than 0.05, it can be concluded that the pretest and posttest data are normally distributed. The test results show that there is an average difference of 4.640, with a standard error of the mean of 0.244 and a t-value of 19.006. The Sig value (2-tailed) is 0.000, which indicates that the difference between the pretest and posttest is statistically significant. The zig-zag dribbling training method has a significant influence on improving the dribbling skills of players in the 13-15 year age group at SSB Buazh FC Magetan.